2021
DOI: 10.1016/j.medcli.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of myocardial injury in a cohort of patients with SARS-CoV-2 infection

Abstract: BACKGROUND: Myocardial injury has been identified as a common complication in patients with COVID-19. However, recent research has serious limitations, such as non-guideline definition of myocardial injury, heterogenicity of troponin sampling or very short-term follow-up. Using data from a large European cohort, we aimed to overcome these pitfalls and adequately characterize myocardial damage in COVID-19. METHODS: Consecutive patients with confirmed SARS-CoV-2 infection and available high-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…In addition, studies have also shown a correlation of elevated serum troponin levels and a higher risk of myocardial injury and substantially higher mortality in COVID-19 patients (Knight et al, 2020;Shi et al, 2020;Wei et al, 2020;Caro-Codón et al, 2021). Notably, in a large study with 1,053 patients with COVID-19 in whom troponin-I, B-type natriuretic peptide, C-reactive protein, ferritin, and D-dimer were measured, only troponin was identified as the only independent predictor of 30-days mortality (Manocha et al, 2021).…”
Section: Long Term Consequences Of Covid-19 On the Heartmentioning
confidence: 99%
“…In addition, studies have also shown a correlation of elevated serum troponin levels and a higher risk of myocardial injury and substantially higher mortality in COVID-19 patients (Knight et al, 2020;Shi et al, 2020;Wei et al, 2020;Caro-Codón et al, 2021). Notably, in a large study with 1,053 patients with COVID-19 in whom troponin-I, B-type natriuretic peptide, C-reactive protein, ferritin, and D-dimer were measured, only troponin was identified as the only independent predictor of 30-days mortality (Manocha et al, 2021).…”
Section: Long Term Consequences Of Covid-19 On the Heartmentioning
confidence: 99%
“…Myocardial injury is an important pathogenic feature of COVID-19, where cardiovascular histopathology findings are reported in up to 48% of patients; moreover, cardiovascular magnetic resonance abnormalities are detected in 26% to 60% of recovered hospitalized patients [ 687 , 688 , 689 , 690 ]. The frequent presence of elevated high-sensitive troponin I (hs-TnI) in COVID-19 patients is significantly associated with higher rates of cardiac complications [ 691 ]. Even though immune-mediated inflammation and hypercoagulability [ 692 ], the dysregulation in the CD147-cyclophilin pathway [ 693 ], as well as other potential direct and indirect mechanisms have been proposed [ 694 ], the exact causal mechanisms for myocardial injury in COVID-19 still await further elucidation [ 695 ].…”
Section: Melatonin Regulates Sars-cov-2-mediated Crosstalk Between Th...mentioning
confidence: 99%
“…It has been shown that myocardial damage occurs in about 20% of patients with severe COVID-19 ( 26 ). In such circumstances, even mild increases of cTnI (well below the 99th percentile) are associated with a higher prevalence of cardiac and non-cardiac complications, and a higher mortality ( 8 , 27 ). In 2,700 patients with severe COVID-19, signs of myocardial injury were common and usually associated with mild elevations in troponin concentration ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that increased troponin levels in patients with severe (1) COVID-19 are associated with an increased likelihood of cardiovascular disease, critical illness (2, 3), and death (4,5). Patients with COVID-19 not only show troponin levels above the 99th percentile more frequently, but also show measurably increased levels of troponins (below the 99th percentile but above the limit of detection) more frequently (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%